ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS (Studi Kasus Pasien Rawat Jalan Di Rumah Sakit Umum Daerah Nganjuk) - Diah Rahmawati; Abu Talkah (Universitas Islam Kadiri, 2019)
This study specifically discusses the relationship between service quality, satisfaction and loyalty at outpatient RSUD Nganjuk. The aim of this study are : 1) To know the effect of service quality to satisfaction of the outpatients RSUD Nganjuk, 2) To know the effect of service quality to loyalty of the outpatients RSUD Nganjuk, 3) To know the effect of satisfaction to loyalty of the outpatients RSUD Nganjuk. There were 150 respondents in these research within their criteria has passing senior high school degree and more than two times taking outpatient or accompanying outopatient's at RSUD Nganjuk. The sample deciding method is purposive sampling. To gain the result as the research goal, structural equation modelling SEM were analyzed by analysis moment of structure (AMOS) and special package for statistic science (SPSS) The results shows that : 1) Service quality positive and significantly effects the satisfaction of the outpatient RSUD Nganjuk, 2) Service quality positive and significantly effects the loyalty of the outpatient RSUD Nganjuk and 3) Satisfaction positive and significantly effects the loyalty of the outpatient RSUD Nganjuk.